Issues in Global Supply Chain with a Focus on the UAE: Logistics and Security Concerns - KAHEEL, MOHAMED SOLAIMAN (2013)
Fragmentation of production has made efficient logistics a must for a successful supply chain. Having good logistics, thus, is becoming increasingly important for all countries to enable them to participate in global supply chains and attract foreign investments that contribute to economic developments. Also, Globalization makes global supply chains vulnerable to security challenges as the world is becoming more interconnected, and a certain threat in one country could disrupt the whole supply chain. This paper aims to explore the state of logistics in the world and its role in international trade, particularly in the top performing countries, and compare it with its equivalent in the United Arab Emirates. The impact of logistics on the global supply chain will be discussed, and some of the security concerns in the world and in the UAE are examined.